Menelisik Stres Kerja Tenaga Kesehatan Dimasa Pandemi Covid-19 di Rumah Sakit - Cokorda Istri Inten Purwaningsih; Gede Sri Darma (Universitas Pendidikan Nasional, 2021)
This study aims to determine the factors that cause stress levels, resilience factors, and barriers for health workers in dealing with Covid-19 patients at the Denpasar City Hospital. This study uses a descriptive qualitative approach. Data was collected by using interviews, observation, and documentation techniques. Data analysis techniques include data reduction, data presentation, and drawing conclusions. Checking the validity of the data was carried out by displaying the participation of researchers, triangulation techniques using various sources, anchovies and methods, and persistence of observation. Research informants are doctors and nurses. The results showed that: The factors that influence the stress of health workers in dealing with Covid-19 in Denpasar City hospitals are the heavy workload during the pandemic, the lack of quality of work support facilities for health workers and the stigma of society towards health workers. The factors possessed by medical personnel for resistance to stress are the presence of self-motivation in the form of mindfulness and moral and professional responsibility as health workers, motivation from the patient's family as well as motivation and support from the organization. The obstacles encountered by health workers are the lack of quality and quantity of work support facilities and various patient behaviors that hinder the healing process of Covid-19 patients.